Moderasi Opini Audit pada Pengaruh Ketergantungan dan Kemandirian Daerah terhadap Pengungkapan LKPD Indonesia 2020–2023 - Yulida Army Nurcahya; Martiana Riawati Utami; Ghiyats Furqon Dewantara (Owner : Riset dan Jurnal Akuntansi, 2026)
Transparency and accountability of regional finances are crucial elements of good governance. However, the level of mandatory disclosure in the Regional Government Financial Report (LKPD) has not yet reached 100%. One factor that can influence the level of disclosure is the level of regional dependence and independence in financial management. This study aims to examine the effect of regional dependence and independence on the level of mandatory disclosure in the LKPD, with audit opinion as a moderating variable. Audit opinion plays a crucial role in assessing the quality of financial reports and can strengthen or weaken the relationship between regional dependence and independence and LKPD disclosure. The research method used in this study was purposive sampling with a total sample of 136. The results show that regional independence has a significant positive effect, while the level of dependence does not directly affect disclosure. Audit opinion has been shown to moderate both relationships. This study is expected to provide academic contributions in the field of public sector accounting auditing and provide consideration for regional governments in improving regional financial transparency and accountability.